Selective late sodium current inhibitor GS‐458967 suppresses Torsades de Pointes by mostly affecting perpetuation but not initiation of the arrhythmia. (6th May 2018) - Bossu, Alexandre; Houtman, Marien J C; Meijborg, Veronique M F; Varkevisser, Rosanne; Beekman, Henriette D M; Dunnink, Albert; de Bakker, Jacques M T; Mollova, Nevena; Rajamani, Sridharan; Belardinelli, Luiz; van der Heyden, Marcel A G; Vos, Marc A
Abstract : Background and Purpose: Enhanced late sodium current (late I Na ) in heart failure and long QT syndrome type 3 is proarrhythmic. This study investigated the antiarrhythmic effect and mode of action of the selective and potent late I Na inhibitor GS‐458967 (GS967) against Torsades de Pointes arrhythmias (TdP) in the chronic atrioventricular block (CAVB) dog. Experimental Approach: Electrophysiological and antiarrhythmic effects of GS967 were evaluated in isolated canine ventricular cardiomyocytes and CAVB dogs with dofetilide‐induced early afterdepolarizations (EADs) and TdP, respectively. Mapping of intramural cardiac electrical activity in vivo was conducted to study effects of GS967 on spatial dispersion of repolarization. Key Results: GS967 (IC50 200nM) significantly shortened repolarization in canine ventricular cardiomyocytes and sinus rhythm (SR) dogs, in a concentration and dose‐dependent manner. In vitro, despite addition of 1μM GS967, dofetilide‐induced EADs remained present in 42% and 35% of cardiomyocytes from SR and CAVB dogs, respectively. Nonetheless, GS967 (787±265nM) completely abolished dofetilide‐induced TdP in CAVB dogs (10/14 after dofetilide to 0/14 dogs after GS967), while single ectopic beats (sEB) persisted in 9 animals. In vivo mapping experiments showed that GS967 significantly reduced spatial dispersion of repolarization: cubic dispersion was significantly decreased from 237±54ms after dofetilide to 123±34ms after GS967. Conclusion and Implications: GS967 terminated all dofetilide‐induced TdP without completely suppressing EADs and sEB in vitro and in vivo, respectively. The antiarrhythmic mode of action of GS967, through the reduction of spatial dispersion of repolarization, seems to predominantly impede the perpetuation of arrhythmic events into TdP rather than their initiating trigger.